Laboratory Diagnosis Of Sarcoidosis - Dutta S.K; Gupta S.K; Chattopadhyay A (Wolters Kluwer Medknow Publications, 2001)
Sarcoidosis is not an uncommon disease. Unfortunately, the awareness amongst clinicians is lacking and due to overwhelming prevalence of tuberculosis, a disease with many similar features, the diagnosis is missed and often delayed. The gold standard investigation finding in the diagnosis of sarcoidosis is the presence of noncaseating tuberculoid granuloma, also known as sarcoid or sarcoid-like granuloma. Some classical chest X-ray findings, clinico-radiological dissociation. Suggestive organ lesions, negative Mantoux test (MT), development of MT site granuloma, hypercalcemia, hypercalciuria and raised serum angiotensin converting enzyme (SACE) value and negative tests for tuberculosis are usually hekpful in the diagnosis of sarcoidosis.